Identification of genes involved in verazine biosynthesis in Veratrum grandiflorum and their heterologous production in Saccharomyces cerevisiae - Kaiyun Hong; Xiangyu Liu; Changqing Wang; Yanjiao Xu; Guisheng Xiang; Shengchao Yang; Jianli Yang; Guanghui Zhang; Simei He (BMC Plant Biology)
Abstract Verazine is a verazine-type alkaloid primarily found in plants of the family Melanthiaceae. In addition to its direct antifungal activity, it serves as a key precursor in the biosynthesis of cyclopamine, a potent inhibitor of the Hedgehog signaling pathway. In this study, we sequenced the transcriptomes of Veratrum grandiflorum roots treated with methyl jasmonate, genes involved in verazine biosynthesis VgCYP90B27, VgCYP94N1, VgCYP90G1, and VgGABAT, were characterized. We produced verazine using Saccharomyces cerevisiae chassis with a yielding 71.62 ± 3.50 µg/L. Furthermore, the GAME4 gene with aldeylation of C-26 was also introduced, and the flask fermentation titer was increased to 175 ± 1.38 µg/L, which was the highest titer reported so far. These results provide a reference for high efficient heterologous biosynthesis study of verazine, and lay a foundation for the deciphering of cyclopamine biosynthetic pathway.